The Effect of Temperature on Porang (Amorphophallus oncophyllus) Moisture Content and Drying Rate Using a Tray Dryer - Karina Kusuma Wardani; Nur Ihda Farikhatin Nisa; Mohammad Arfi Setiawan; Erlinda Ningsih (Agroindustrial Technology Journal, 2023)
Porang (Amorphophallus oncophyllus) is a tuber plant originating from Indonesia. This plant is less well known compared to other tuber plants. Porang has various important uses, especially in the food and industrial sectors. Indonesia ranks 5thas the largest supplier of porang in the world. Drying porang is an important stage in the post-harvest processing of porang plants. The drying process must be done carefully so as not to damage the quality of the porang. The right drying method, appropriate drying temperature, and humidity control must be considered to achieve optimaldrying results. A tray dryer is a drying device that contains shelves to store the material being dried. Drying with this tool uses hot air gusts that are passed over the material being dried. The aim of this research is to determine the effect of drying temperature variations on the moisture content and drying rate of porang using a laboratory-scale tray dryer. Drying is carried out on stick-shaped porang with a thickness of 1 cm and a total weight of 125 grams. The temperature variations in this drying are 50OC, 60OC, and 70OC, with a drying air speed 1 m/s. The research results show that the higher the drying air temperature in the tray dryer, the lower the moisture content in the porang and the faster the drying rate. When the drying air speed and porang thickness are constant, the optimal porang drying temperature is 70OC